Religion and Caregiving for Orphans and Vulnerable Children: A Qualitative Study of Caregivers Across Four Religious Traditions and Five Global Contexts - Eagle, David E. (Journal of religion and health, 2020)
Studies of caregivers of orphans and vulnerable children (OVC) rarely examine the role religion plays in their lives. We conducted qualitative interviews of 69 caregivers in four countries: Ethiopia, Kenya, Cambodia, and India (Hyderabad and Nagaland), and across four religious traditions: Christian (Orthodox, Roman Catholic, and Protestant), Muslim, Buddhist, and Hindu. We asked respondents to describe the importance of religion for their becoming a caregiver, the way in which religion has helped them make sense of why children are orphans, and how religion helps them face the challenges of their occupation. Using qualitative descriptive analysis, three major themes emerged. Respondents discussed how religion provided a strong motivation for their work, reported that religious institutions were often the way in which they were introduced to caregiving as an occupation, and spoke of the ways religious practices sustain them in their work. They rarely advanced religion as an explanation for why OVC exist - only when pressed did they offer explicitly religious accounts. This study has implications for OVC care, including the importance of engaging religious institutions to support caregivers, the significance of attending to local religious context, and the vital need for research outside of Christian contexts.